Immune response in patients with cancer pain - Golubović, Vesna, liječnica (Array, 2009)
The role of perioperative pain management techniques on immune functions in patients with malignancies is still poorly understood. Although the suppression of cellular and humoral immune response in carcinoma patients is a subject of great scientific interest, we know very little about the changes in innate immunity (natural killer T cells-NKT cells, regulatory T cells-Tregs) following tumor growth, as well as in acquired immunity and cytotoxic functions of NK cells in these patients undergoing surgery and the involvement of different perioperative analgesia techniques.